Editorial letter - Medina Bañuelos, Veronica (Revista Mexicana de Ingenieria Biomedica, 2015)
DEAR READERS, We present the number 2 of volume 36, corresponding to the May-August period of 2015. In this issue interesting contributions related to the acquisition and processing of electrophysiological signals, segmentation of ultrasound images and computer-assisted surgery are presented. In addition, a special issue is being prepared dedicated to contributions of science and technology development specially designed for the elderly. It has been a challenge for the RMIB to maintain the quarterly periodicity initiated in 2013 and the required punctuality to have each number ready at the beginning of the corresponding period. But we hope, with these measures, to increase the fluency for the community to present its results and hence their impact, reflected through citations of published articles. Also, the support group of the RMIB has continued its efforts to include the RMIB in REDALyC and ISI Thompson Reuters and to preserve its membership to those indices to which the RMIB already belongs to. Best regards from the RMIB Editorial Committee.